Country Indicators Moderating the Relationship Between Phubbing and Psychological Distress: A Study in 20 Countries - Błachnio, Agata; Przepiórka, Aneta; Gorbaniuk, Oleg; McNeill, Monika; Bendayan, Rebecca; Durak, Mithat; Senol-Durak, Emre; Ben-Ezra, Menachem; Benvenuti, Martina; Angeluci, Alan; Abreu, Ana Maria; Makita, Meiko; et al. (Frontiers in Psychology, 2021)
Using a mobile phone in a problematic way can be related to negative mental states. Some studies indicate that behavioural dependency is related to the variables associated with a country of origin. The aim of our study was to investigate whether country indicators moderate the relationship between phubbing and psychological distress. Our sample consisted of 7,315 individuals from 20 countries who completed a survey including the following measures: Phubbing Scale, Distress Scale K6 and country indicators such as Gender Gap Index (GGI), The Human Development Index (HDI), Social Progress Index (SPI), Hofstede’s dimensions of culture, and World Happiness Index (WHI). Our results showed that psychological distress is related to phubbing dimensions (communication disturbance and phone obsession) and these associations are found to be consistent across countries, therefore culturally universal. However, amplifying or weakening the effect between phubbing and distress is associated with some indices on a cultural level. cultural level.